Properties of cross-laminated oriented bamboo scrimber board (CL-OBSB) - Chung, Min-Jay; Wang, Sheng-Yang (Bioresources, 2023)
Physical and mechanical properties were evaluated for cross-laminated oriented bamboo scrimber board (CL-OBSB). Results of non-destructive testing revealed a linear relationship of parallel grain content with ultrasonic-wave velocity, dynamic modulus of elasticity (DMOEu), tap-tone velocity, and DMOEt values. In terms of the ratio of parallel grain, CL-OBSB 80%(//) possessed the highest modulus of elasticity and modulus of rupture values along with the greatest strength. The high grain content compressed in a parallel direction contributed to superior strength performance. Regarding the perpendicular compressive (C┴) strength, because both the CL-OBSB 40%(//) configuration and CL-OBSB have a mid-layer consisting of 60% parallel grain, CL-OBSB 40%(//) holds the largest C┴ value. Furthermore, the shear bond strength (S) showed that the S// value was 1.03 times that of the S┴ value with a wood failure frequency of 97%. After the dimensional stability test, the water absorption and volumetric swelling of the four CL-OBSB types ranged between 15.3% and 17.7% and 9.5% to 10.6%, respectively. In conclusion, the orthogonal configuration of CL-OBSBs can improve balance expansion and contraction in different directions, thus increasing its dimensional stability.